Corporeality Education in Latin America and the Global South: The body as a socio-educational strategy for the well-being of the human being - Navarrete Ávila, M. Sc. Marco Antonio (Transformación, 2021)
Objective: The paper suggests to consider the inclusion of the body and corporeality in socioeducational contexts for the integral well-being of human beings and society and for understanding the value of corporeality education in the processes of learning and creativity. Method: bibliographic review, critical method with updated reference to databases. Results: Rethinking contemporary education should be seen as a new way to educate anyone. Educating is a mysterious art that values individuality and human diversity. Education in Latin America and the Global South presents Eurocentric biases associated with The western colonialist epistemology of the Global North (De Sousa, 2015), inhibiting the pedagogies that value the body, corporeality and creativity of communities and territories. The enrichment presented by this pedagogical gaze seeks to build new senses and meanings of the body and on the body that is educated, increasing the sensitivity and listening of those corporeality that have been systematically silenced and omitted (Aguila y López, 2019). Conclusion: The body and its corporeality is addressed by multiple dimensions and concepts in contemporary education, however, it is essential to revalue its importance in educational practices in order to reduce school segregation (understood as a problem of social and political background in the face of discrimination given by the domination of the hegemonic discourse of the western colonialist epistemology of the Global North), in order to finally promote human development in socio-educational practices from a genuine inclusive approach.